2011
DOI: 10.1017/s1368980011001212
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and construct validity of Mediterranean diet scores as assessed by an FFQ

Abstract: Objective: The aim of the present study was to assess the concurrent and construct validity of two diet-quality indices, a modified Mediterranean diet score (mMDS) and a Mediterranean-like diet score (MLDS) additionally incorporating unhealthy food choices, as determined by an FFQ. Design: A validation study assessing FFQ intake estimates compared with ten or more unannounced 24 h recalls. Pearson's correlation coefficients, intraclass correlation coefficients (ICC), Bland-Altman plots and the limits of agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
52
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 26 publications
14
52
0
4
Order By: Relevance
“…The correlation between the DHD-index based on FFQ data and based on 24hR data was comparable with the correlation ( r 0·48) reported by Benítez-Arciniega et al ( 30 ) , who compared the ‘Modified Mediterranean diet score’ based on FFQ data with the score based on twelve 24hR. However, our observed correlation was lower than the correlation ( r 0·72) reported by Newby et al.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The correlation between the DHD-index based on FFQ data and based on 24hR data was comparable with the correlation ( r 0·48) reported by Benítez-Arciniega et al ( 30 ) , who compared the ‘Modified Mediterranean diet score’ based on FFQ data with the score based on twelve 24hR. However, our observed correlation was lower than the correlation ( r 0·72) reported by Newby et al.…”
Section: Discussionsupporting
confidence: 88%
“…Well over a half of the participants in the present study were classified into the same tertile; this result is similar to the results from cross-classifications between a FFQ and 24hR on food groups ( 30 , 31 ) . Furthermore, Kendall's τ-b coefficient showed a moderate agreement between the tertiles of the DHD-index based on FFQ and 24hR data.…”
Section: Discussionsupporting
confidence: 87%
“…The validation study of an FFQ almost identical to the one used in the CAPS study showed low to moderate correlation for several food items ( 19 ) ; however, high correlation coefficients between FFQ and food records are rarely achieved ( 58 ) . Another study validating a modified MDS version assessed by an FFQ against 24-h recalls showed a Pearson's correlation coefficient of 0·48, and the average FFQ-based score was 102 % of the recall-based score ( 59 ) . In the present study, the use of energy-adjusted dietary intake reduces the potential influence of bias due to measurement error.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intake data derived from a validated full-length food frequency questionnaire (FFQ) 10,11 were employed to simulate responses that would have been obtained using the sDQS. The DQI derived from the simulated data was calculated, as described in the validation study.…”
Section: Methodsmentioning
confidence: 99%